Prednisolone pharmacokinetics in dogs with protein‐losing enteropathy - Sara A. Jablonski; Jessica L. Strohmeyer; John P. Buchweitz; Andreas F. Lehner; Daniel K. Langlois (Journal of Veterinary Internal Medicine)
Abstract Background It is unknown if glucocorticoid malabsorption contributes to the approximate 50% treatment failure rate in dogs with protein‐losing enteropathy (PLE). Objective To compare pharmacokinetics (PK) of orally administered prednisolone in dogs with PLE vs healthy controls. Animals Fourteen dogs with well‐characterized PLE and 7 control dogs. Methods Prospective case‐controlled study. Dogs were treated with 1 mg/kg prednisolone PO once daily for approximately 3 weeks. Venous blood samples were collected at set timepoints before and after prednisolone administration on the first (T1) and final (T2) study days. Total and non‐protein bound serum prednisolone concentrations were determined using liquid chromatography tandem‐mass spectrometry, and pharmacokinetics variables were derived from the drug concentration data. Pharmacokinetics variables were compared between PLE and control dogs and between PLE short‐term responders and non‐responders. Results The PLE dogs had a shorter half‐life of the terminal slope than control dogs (harmonic mean of 1.3 vs 1.8 hours; P = .05) whereas the percentage of serum prednisolone that was non‐protein bound was higher in PLE dogs than in control dogs (median of 15.7% vs 6.7%; P = .02) at T1. Total prednisolone drug exposures and maximum total serum drug concentrations did not differ between PLE and control dogs at T1 or T2, nor did they differ between short‐term responders and non‐responders within the PLE population (P > .05 for all comparisons). Conclusions and Clinical Importance Overall drug exposures are similar between PLE dogs and healthy controls. Glucocorticoid malabsorption is unlikely to be a common cause of treatment failure in dogs with PLE.